Measurement of Right and Left Ventricular Ejection Fractions by Gated Equilibrium Scintigraphy Using Fourier Functional Images - Franquiz, J. M; Cardenas, R.; Lord, E.; Garcia-Barreto, D. (Nuklearmedizin - NuclearMedicine, 1982)
Left and right ventricular ejection fractions (LVEF and RVEF) were calculated by gated equilibrium scintigraphy in 28 normal controls and in 21 patients with heart disease. Regions of interest (ROIs) for the ventricles were assigned on the amplitude and phase Fourier images. Two methods of preprocessing of data were compared. In Method 1 the resolution was improved and the statistical noise was reduced, while in Method 2 only the statistical noise was reduced. There were no differences between the results of the two methods for the left ventricle. The mean LVEF for normal subjects was 0.63 ± 0.06. For the right ventricle, Method 1 showed higher sensitivity in detecting reduced RVEF in pathological situations. The mean RVEF by Method 1 for normal controls was 0.56 ± 0.07, which is significantly different (p < 0.001) than that found by Method 2 (0.36 ± 0.05), and similar to those reported by others employing the firstpass method. The results show the usefulness of the phase Fourier image and the importance of a suitable preprocessing of data for determining RVEF by gated equilibrium scintigraphy.